The relationship between new product creativity components and purchase intention and the mediating impact of perceived values: a study of consumers in Ho Chi Minh city - Tho Phuoc Vo; Mai Dong Tran; Thi Minh Chau Ly (Cogent Business & Management, 2022)
This study aims to extend creativity literature based on consumers' perspective by examining empirically the effects of new product creativity dimensions of novelty and meaningfulness on consumers' purchase intention with the mediating roles of perceived values, consisting of perceived hedonic value and perceived utilitarian value. Data were collected via an online approach due to the lockdown in Ho Chi Minh City. Based on testing hypotheses by using structural equation modeling and a sample that included 221 respondents, the results indicate that novelty and meaningfulness do not affect consumers' purchase intentions directly. Instead, novelty affects indirectly consumers' purchase intention through impacting perceived hedonic value, while meaningfulness influences perceived utilitarian value which in turn, affects consumers' purchase intentions. These results offer crucial guidelines for firms and managers to develop new products and promotional strategies more efficiently. Finally, managerial implications and directions for future study are presented based on the findings.
Keywords: 650; hedonic value; meaningfulness; new product creativity; novelty; purchase intention; utilitarian value